Efektivitas Model Pembelajaran Probing Prompting dan Numbered Heads Together (NHT) Terhadap Kemampuan Berpikir Kritis - Septarina, Eva; Sodikin, Sodikin; AD, Yahya (Indonesian Journal of Science and Mathematics Education, 2019)
Abstract: This study was conducted to find out (1) is there any influence of the probing prompting and numbered heads together learning model on students 'critical thinking abilities (2) which is the more effective learning model between the prompting and numbered heads together probing learning model on students' critical thinking skills . This research is a Quasi Experimental Design. The population in this study was all class X SMA N 1 Tiga Reviewed, the sampling technique was random sampling technique. The sample in this study used 2 classes, class X Mipa1 as the experimental class 1 and class X Mipa 2 as the experimental class 2. Testing the hypothesis using the t-test, with a significance level of 5%. Then the effectiveness is known by the effect size test which is obtained d = 0.69. then these results are interpreted using the table effect size, the percentage data of 73% is included in the medium category. It was concluded that (1) the probing prompting and numbered heads together learning model had a good influence on students 'critical thinking abilities (2) probing prompting and numbered heads together models were effective in improving students' critical thinking skills.Abstrak: Penelitian ini dilakukan untuk mengetahui (1) adakah pengaruh model pembelajaran probing prompting dan numbered heads together terhadap kemampuan berpikir kritis peserta didik (2) manakah model pembelajaran yang lebih efektif antara model pembelajaran probing prompting dan numbered heads together  terhadap kemampuan berpikir kritis peserta didik. Penelitian ini merupakan Quasi Eksperimen Design. Populasi dalam penelitian ini adalah seluruh kelas X SMA N 1 Tiga Dihaji, Teknik pengambilan sampelnya yaitu teknik  random sampling. Sampel dalam penelitian ini menggunakan 2 kelas,  kelas X Mipa1 sebagai kelas eksperimen 1 dan kelas X Mipa 2 sebagai kelas eksperimen 2. Pengujian hipotesis menggunakan uji-t, dengan taraf signifikasi 5%. Kemudian keefektifan diketahui dengan uji effect size yaitu memperoleh nilai d =0,69. kemudian hasil ini diinterprestasikan dengan menggunakan tabel effect size diperoleh data presentase sebesar 73% termasuk dalam kategori sedang. Diperoleh kesimpulan bahwa (1) model pembelajaran probing prompting dan numbered heads together memberikan pengaruh yang baik terhadap kemampuan berpikir kritis peserta didik (2) model probing prompting dan numbered heads together  efektif dalam meningkatkan kemampuan berpikir kritis peserta didik.